Micromechanical vibration absorber for frequency stability improvement of DETF oscillator. (22nd February 2019) - Du, Jianshu; Wei, Xueyong; Ren, Juan; Wang, Jiuhong; Huan, Ronghua
Abstract: This article explores a novel way to improve the frequency stability of micromechanical double-ended tuning fork (DETF) resonators. The aim of this work is to use a non-linear vibration absorber to improve the frequency stability of the oscillator. A vibration absorption device is set up on the oscillator to absorb part of the energy of the oscillator. The influence of the vibration absorber on the frequency stability is studied. The short-term frequency stability of the DETF oscillator can be improved from 378 ppb to 202 ppb by coupling it to a mechanical vibration absorber.